Corporate Social Responsibility Dalam Memoderasi Pengaruh Profitabilitas, Likuiditas Dan Kebijakan Dividen Terhadap Nilai Perusahaan Barang Konsumsi Subsektor Makanan Dan Minuman Yang Terdaftar Di BEI Periode 2019-2023 - Indriyani, Lisa; Novietta, Liza; Nurmadi, Ruswan (Worksheet : Jurnal Akuntansi, 2025)
This research aims to determine Corporate Social Responsibility in moderating the effect of Profitability, Liquidity and Dividend Policy on the Firm Value of consumer goods companies in the food and beverage sub-sector listed on the IDX for the 2019-2023 period. The sample in this study was 19 food and beverage sub-sector companies in the 2019-2023 period. The data analysis technique used was multiple linear regression analysis and moderated regression analysis (MRA) test with statistical data processing using the SPSS data processing application version 26.0. The results of this study indicate: (1) Profitability proxied using Return On Equity has a positive and significant effect on Firm Value, (2) Liquidity proxied using Current Ratio has a positive and significant effect on Firm Value, (3) Dividend Policy proxied using Dividend Payout Ratio has a positive and significant effect on Firm Value, (4) Corporate Social Responsibility (CSR) has a positive but insignificant effect on Firm Value, (5) Corporate Social Responsibility (CSR) is unable to moderate the influence of Profitability on Firm Value, (6) Corporate Social Responsibility (CSR) is unable to moderate the influence of Liquidity on Firm Value, (7) Corporate Social Responsibility (CSR) is unable to moderate the influence of Dividend Policy on Firm Value.